Angus, thongs and perfect snogging - Chadha, Gurinder; Obst, Lynda, 1950-; Berges, Paul Mayeda; McRobb, Will; Viscardi, Chris; Groome, Georgia; Tomlinson, Eleanor, 1992-; Rennison, Louise; Paramount Pictures Corporation; Nickelodeon Movies; Goldcrest Pictures; Copyright Collection (Library of Congress) (United States : Paramount Pictures, 2008)
"Director Gurinder Chadha explores the world of precocious adolescent girls with this tale of a quirky teen whose mind perpetually drifts back to thoughts of growing up, procuring the perfect boyfriend, and throwing the biggest birthday bash ever. While maintaining the perfect social life or getting that nose job she so desperately wants were once her highest priorities in life, the girl who wanted it all gradually discovers that family and friends are more important than any popularity contest"--Allmovie.com, October 25, 2018.
Based on the novel written by Louise Rennison.
Aspect ratio is 2.35:1.
Not viewed.
Sources used: Copyright staff catalog, viewed August 24, 2016; Weekly Variety, July 28, 2008; Internet movie database WWW site, viewed August, 24, 2016.
Sources used: Copyright catalog online; Copyright description; Internet movie database, October 25, 2018; Variety, July 28, 2008; Studiosystem.com, October 25, 2018.
Executive producer, Scott Aversano ; camera, Richard Pope ; editors, Martin Walsh, Justin Krish ; music, Joby Talbot ; production designer, Nick Ellis ; costume designer, Jill Taylor ; sound, Tim Fraser.
Keywords: Teenage girls -- United States -- Drama; High school students -- United States -- Drama; Birthday parties -- United States -- Drama; Teen films; Coming-of-age films; Comedy films; Feature films; Fiction films